Answer:
2(a - 4) + 5(b + 1) = 8. The result of this equation when solving is a = - 5b/2 + 11/2.
3(a - 1) - 2(b - 2) = -11. The result of this equation when solving is a = 2b/3 - 4.
Step-by-step explanation:
Hope this helps =)
Z = 3 (This equation is a given)
z(y) = 12 ( This equation is also given)
3y = 12 (as z = 3, plug 3 into z)
3y/3 = 12/3 (isolate the y by dividing 3 to both sides)
* you divide 3 to both sides because of the equal sign. What you do to one side you do to the other
y = 4 (answer for y)
y + 5 (what you are solving for)
(4) + 5 = 9 (As y = 4, plug in 4 for y in this equation)
y + 5 = 9 (4 + 5 = 9, or addition property)
9 is your answer
hope this helps
Answer:
wait wait explain on what i need to do
Step-by-step explanation: